46.7k views
4 votes
Show all work: Solve the equation: 8(x + 2) – 3(3x + 4) = -1

And Show all work: Solve the equation: 10b + 2 – 5b = 2 – 5(b + 8)

And Show all work: Solve the Equation: 0.3(x – 6) = 0.2x + 0.5x + 7 - 4

1 Answer

1 vote

Answer:

Part A: x = 5

Part B: b = -4

Part C: x = -12

Explanation:

Part A:

8(x + 2) – 3(3x + 4) = -1

8x + 16 - 9x - 12 = -1

-x + 4 = -1

-x = -5

x = 5

Part B:

10b + 2 – 5b = 2 – 5(b + 8)

5b + 2 = 2 - 5b - 40

10b + 2 = 2 - 40

10b + 2 = -38

10b = -40

b = -4

Part C:

0.3(x – 6) = 0.2x + 0.5x + 7 - 4

0.3x - 1.8 = 0.7x + 3

0.3x - 0.7x = 3 + 1.8

-0.4x = 4.8

x = -12

Hope this helps! I apologize if I'm incorrect.

User Gogu CelMare
by
6.0k points